Solid waste management by coastal communities of the Gulf of Nicoya (Biocenosis, 2023)
The objective of this article is to describe the situation of solid waste management in some coastal communities of the Gulf of Nicoya. This marine area is one of the richest in diversity in the country; a large amount of fishery resources has been extracted from its waters, contributing significantly to food security and the national economy. However, for many years, this abundant fishing production has been showing alarming symptoms due to high levels of water pollution mainly due to solid waste. This is increasingly degrading the health and economy of coastal communities. Through interviews conducted in different coastal towns, residents pointed out the inadequate management of solid waste by some municipalities in the gulf. As a result, it was concluded that it would be ideal to establish some partnerships with national and international universities, organizations, and companies to implement environmental education techniques in the communities and conduct water quality assessments to monitor the issue.
Keywords: waste collection; mangrove; nets; awareness; deterioration of landscape.